The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1089/jpm.2007.0102
|View full text |Cite
|
Sign up to set email alerts
|

(Using) Complementary and Alternative Medicine: The Perceptions of Palliative Patients with Cancer

Abstract: Use of complementary and alternative medicine (CAM) is increasingly common within Western societies, including Australia. This parallels calls for or claims of integration of CAM into mainstream medical practice, with oncology and palliative care specifically nominated as appropriate arenas for integration. However, there is an absence of studies examining patient perceptions of both CAM and CAM users. In this study, 28 adult patients with cancer close to death were interviewed regarding treatment decisions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
1
38
0
1
Order By: Relevance
“…As found in another study, some nonusers devalued CAM and lacked confidence in its efficacy 48 . These findings also support the literature that CAM nonusers believed the decision to use CAM was because of distrust with biomedicine 49,50 .…”
Section: Discussionsupporting
confidence: 86%
“…As found in another study, some nonusers devalued CAM and lacked confidence in its efficacy 48 . These findings also support the literature that CAM nonusers believed the decision to use CAM was because of distrust with biomedicine 49,50 .…”
Section: Discussionsupporting
confidence: 86%
“…Mind-body interventions are defined as practices that focus on the interactions among the brain, mind, body, and behavior, with the intent to use the mind to affect physical functioning and promote overall health. The studies reviewed herein were found by means of a multipledatabase search including MEDLINE, PsycARTICLES, therapy/mind-body intervention use to their doctors for fear of offending their doctor [1]. This conclusion has some support as found in the report that some doctors do disapprove of complementary interventions [2,3].…”
Section: Introductionmentioning
confidence: 59%
“…24 Fear of oncologists' disapproval has been shown to be a reason for nondisclosure 5,25 of CAM use and of a reason why some patients with terminal cancer patients not taking CAMs. 26 Do doctors know what their patients are taking? Past work has shown that patient disclosure of CAM use to oncologists is in the range of 40%-60%.…”
Section: Cam Use With Radiotherapymentioning
confidence: 99%